SARS-CoV-2 Virus Culture and Subgenomic RNA for Respiratory Specimens from Patients with Mild Coronavirus Disease - Perera, Ranawaka A.P.M.; Tso, Eugene; Tsang, Owen T.Y.; Tsang, Dominic N.C.; Fung, Kitty; Leung, Yonna W.Y.; Chin, Alex W.H.; Chu, Daniel K.W.; Cheng, Samuel M.S.; Poon, Leo L.M.; Chuang, Vivien W.M.; Peiris, Malik (Emerging infectious diseases, 2020)
We investigated 68 respiratory specimens from 35 coronavirus disease patients in Hong Kong, of whom 32 had mild disease. We found that severe acute respiratory syndrome coronavirus 2 and subgenomic RNA were rarely detectable beyond 8 days after onset of illness. However, virus RNA was detectable for many weeks by reverse transcription PCR.